1998
DOI: 10.1093/ndt/13.12.3118
|View full text |Cite
|
Sign up to set email alerts
|

Long-term experience with an ultrapure individual dialysis fluid with a batch type machine

Abstract: The setup described permits individualized therapy of high quality. The high serum albumin values and our very low incidence of carpal tunnel syndrome underline the importance of water and dialysate quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 0 publications
5
33
1
Order By: Relevance
“…0.05). Similar results were reported by Kleophas et al [13], who analyzed the incidence of CTS in patients treated for up to 13 years predominantly with Cuprophan dialyzers and an ultrapure dialysate produced by a special dialysis system with individual reverse osmosis and ultraviolet irradiation of dialysate (GENIUS ® ). The cumulative incidence of CTS after 13 years was 15%.…”
Section: Clinical Consequences Of Contaminated Dialysis Fluidsupporting
confidence: 84%
“…0.05). Similar results were reported by Kleophas et al [13], who analyzed the incidence of CTS in patients treated for up to 13 years predominantly with Cuprophan dialyzers and an ultrapure dialysate produced by a special dialysis system with individual reverse osmosis and ultraviolet irradiation of dialysate (GENIUS ® ). The cumulative incidence of CTS after 13 years was 15%.…”
Section: Clinical Consequences Of Contaminated Dialysis Fluidsupporting
confidence: 84%
“…In an uncontrolled series with 399 patients, we reported about long-term survival in our center which was observed about 10-20% higher than in other published series [15] (fig. 5).…”
Section: Clinical Experiencecontrasting
confidence: 50%
“…Technical designs of the system have been described [14][15][16]. The Genius ® batch machine receives fresh dialysis fluid from a special automated filling station.…”
Section: Treatment Proceduresmentioning
confidence: 99%
“…If one believes in the importance of ultrapure dialysate, of individualized dialysate electrolyte composition and of ultrafiltration control, one will not be surprised to see that in the uncontrolled series of Kleophas et al [4] a rate of long-term patient survival was observed which was about 10-20% higher than in other published series, e.g. the EDTA Registry data.…”
Section: The Clinical Experiencementioning
confidence: 85%